Novel Heuristic Parameters in Coronary Artery Disease Prevention and Treatment - Arokiaraj, Mark Christopher (Technium BioChemMed, 2026)
There are many factors associated with the incidence and progression of coronary artery disease. Still, the exact mechanisms and pathophysiology are not clearly understood. The process of atherosclerosis remains an enigma, though some basic mechanisms and pathophysiology are known. There are some risk factors associated with clinical conditions that appear protective based on clinical experience. Heuristically, the weightage and performance are represented by the equations. The factors include chronic obstructive lung disease, chronic liver diseases, cataract formation, and chronic renal failure, where the incidence and progression are slower. However, further mechanisms, such as hypoxic-ischemic growth factors with downstream vascular endothelial growth factors (VEGF) and insulin-like growth factors (IGF-1), serum estrogen levels, dystrophic calcification mechanisms, and parathyroid hormone- or calcium-related metabolism through 1,25-dihydroxycholecalciferol, could also play an active role in the etiopathogenesis. Understanding and utilising the underlying pathophysiology and mechanisms can be highly productive for the prevention, progression, and further treatment of coronary artery disease, as well as for future research.